MONEY MARKET AND CAPITAL MARKET RECENT DEVELOPMENTS: INVESTMENT OPPORTUNITIES IN THE DIGITAL ERA - SITI NUR KHOFIFAH (Al-Qalam Institute, Probolinggo, East Java, Indonesia, 2024)
The money market and capital market are two vital components in the global economy which continues to experience rapid development. In this increasingly advanced digital era, technological changes and financial adaptation have created new attractive investment opportunities. In financial markets, recent technologies such as blockchain and smart contracts have changed the way financial transactions are carried out. Improved security and efficiency in payment systems and money transfers have attracted the attention of investors and business people. In addition, technological developments in digital payments, e-wallets and cryptocurrencies have presented new attractive investment opportunities, even though they are still exposed to the risk of high price volatility. The digital era has also opened the door for potential in the startup sector and technology companies. Venture capital and direct investment in innovative technology companies have become a prima donna for investors seeking long-term benefits from changing trends and consumer habits that rely more heavily on technology. However, amid all the opportunities offered by the digital era, there are challenges and risks that need to be considered. Data security and protection is an urgent issue because technological advances also bring more serious potential cyberthreats. In addition, high market volatility, especially in crypto assets, increases investment risk for investors.